PEMBENTUKAN MASYARAKAT MADANI DI INDONESIA MELALUI CIVIC EDUCATION - Farid Wajdi Ibrahim (Jurnal Ilmiah Didaktika, 2012)
Civil society is often positioned as the ideal pattern of community life. From the historical aspect, the Islamic thinkers usually refers to the condition of civil society such as on the condition of Medina under the leadership of the Prophet Muhammad á¹¢allallÄh â€˜alayh wa Sallam. Ideal concept of civil society is driven by a variety of many aspects including the pattern of the life of society, nation that refers to the rule of law, human rights, and respect for diversity in all its forms (pluralism). Certainly not an easy thing to realize the ideal society as the concept of civil society in such a way. It requires a serious effort, continuous and consistent from the variety and facets, one of which is a crucial aspect of civic education (civic education). These issues are the focus of discussion of this article.